PERTUMBUHAN TANAMAN Eucalyptus pellita F. Muell DI LAPANGAN DENGAN MENGGUNAKAN BIBIT HASIL PERBANYAKAN DENGAN METODE KULTUR JARINGAN, STEK PUCUK, DAN BIJI - Ellok Dwi Sulichantini (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Eucalyptus pellita F Muell is a fast-growing tree that has great benefits. The uses of wood are  the raw material  for pulp and paper industry, building construction, and also for charcoal. Propagation can be done by using seeds, cuttings and tissue culture.  Propagation from seed has a weakness for very large offspring genotype variation while the vegetative propagation will produce offspring same with the parent. The Advantages of propagation by tissue culture is able to  produce seedling in large quantities in a short time.The research objective was to determine the growth of Eucalyptus pellita F Muell  seedling in the field  that propagated using three propagation  methods, tissue culture,  cutting,  and seed.The study was conducted in PT Surya Hutani Jaya, Sebulu, Kutai, East Kalimantan.  Seedlings from tissue culture was planted on 13.7 ha,  seedling from cutting was planted on 14.3 ha, and  seedlings from the seeds was planted  on 14.4 ha.  Each seedling was  planted with spacing  3 m x 2.5 m.  All plants had similar treatment in fertilizing, weeding,  pest and disease control. Samples are taken one per cent of the total population of the plant.The results showed that the  plants  from tissue culture seedlings showed the best results on plant height, diameter and volume.